A cost-minimizing approach to eliminating the primary sources of greenhouse gas emissions at institutions of higher education. Issue 3 (16th August 2021) - Timmons, David S.; Weil, Benjamin
Abstract : Purpose: Many institutions of higher education have committed to carbon neutrality. Given this goal, the main economic issue is minimizing cost. As for society as a whole, dominant decarbonization strategies are renewable electricity generation, electrification of end uses and energy efficiency. The purpose of this paper is to describe the optimum combination of strategies. Design/methodology/approach: There are four questions for eliminating the primary institutional greenhouse gas emissions: how much renewable electricity to produce on-site; where and at what price to purchase the balance of renewable electricity required; how to heat and cool buildings without fossil fuels; and how much to invest in energy efficiency. A method is presented to minimize decarbonization costs by equating marginal costs of the alternates. Findings: The estimated cost of grid-purchased carbon-free energy is the most important benchmark, determining both the optimal level of campus-produced renewable energy and the optimum efficiency investment. In the context of complete decarbonization, greater efficiency investments may be justified than when individual measures are judged only by fossil-fuel savings. Practical implications: This paper discusses a theoretically ideal plan and implementation issues such as purchasing carbon-free electricity, calculating marginal costs of conserved energy, nonmarginal cost changes, uncertainty about achieving efficiency targets, and dynamic pricing. The principles described in this study can be used to craft a cost-minimizing decarbonization strategy. Originality/value: While previous studies discuss decarbonization strategies, there is little economic guidance on which strategies are optimal, on how to combine strategies to minimize cost or how to identify a preferred path to decarbonization.